The occurrence of Encarsia perniciosi in areas of northern Greece as assessed by sex pheromone traps of its host Quadraspidiotus perniciosus - Kyparissoudas, D.S. (ENTOMOLOGIA HELLENICA, 1987)
During the 1982-1985 period the aphelinid endoparasite Encarsia perniciosi Tower was captured on synthetic pheromone traps of the San Jose scale (SJS), Quadraspidiotus perniciosus Comstock, in scale-infested insecticide treated and untreated orchards of Central and Western Macedonia (Northern Greece). It has expanded especially near the sites where it had been released, but also in areas 50-100 km from the point of release. The parasite in untreated orchards generally appeared from April to October, while in orchards treated with insecticides it was not caught after mid June. Spring flights of the parasite occurred on almost the same dates as the first captures of the male scale. Subsequent flights of E. perniciosi were not always synchronized with those of the male scale, and after the beginning of June the parasite showed a general decline throughout the remainder of each season. The pheromone of the scale insect acts as a kairomone to the parasite and it can be used in trapping systems in scale-infested orchards for the confirmation of the presence and the distribution of E. perniciosi.